2018
DOI: 10.4103/ajns.ajns_55_17
|View full text |Cite
|
Sign up to set email alerts
|

Intradural disc a diagnostic dilemma: Case series and review of literature

Abstract: Introduction:We present a case series of six cases of intradural disc herniation at L4–L5 level diagnosed on the basis of intraoperative findings.Result:All our cases, on preoperative magnetic resonance imaging (MRI) were reported as having diffuse annular bulge with large posterocentral extrusion. Our study comprised patients in age group of 30–60 years. Four cases out of six presented with cauda equina syndrome. In three cases, cauda equina was associated with sudden deterioration in the power of lower limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…First, they are most likely attributable to adhesions between the posterior longitudinal ligament (PLL), fibrous annulus, and the dural sac; a hole generated through the dura then allows for intradural disc migration. [10,11,14,15] Second, with congenital narrowing of the spinal canal, the decreased available epidural space results in congenital/ iatrogenic thickening of the dura with greater susceptibility to intradural disc rupture. [10,11,14,15]…”
Section: Discussionmentioning
confidence: 99%
“…First, they are most likely attributable to adhesions between the posterior longitudinal ligament (PLL), fibrous annulus, and the dural sac; a hole generated through the dura then allows for intradural disc migration. [10,11,14,15] Second, with congenital narrowing of the spinal canal, the decreased available epidural space results in congenital/ iatrogenic thickening of the dura with greater susceptibility to intradural disc rupture. [10,11,14,15]…”
Section: Discussionmentioning
confidence: 99%
“…Another theory is the "chronic compression" hypothesis. 3 Lee and Fairholm thought that long-term mechanical compression of structures, such as intervertebral discs and osteophytes, could make the dura mater thinner and fragile, facilitating penetration of the dural sac by the nucleus pulposus. 14 Besides, the "adhesions" hypothesis is advocated by some researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, most herniated nucleus pulposi are located epidurally, outside or under the posterior longitudinal ligament. Intradural disc herniation (IDDH), when the nucleus pulposus penetrates the posterior longitudinal ligament (PLL) and the anterior wall of the dura and migrates intrathecally, 3 is very uncommon and accounts for only 0.04-0.33% of all lumbar disc herniations. 4,5 The pathogenesis and natural course of IDDH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Intradural disc herniation is a rare entity reported at 0.04 % to 1.1% by Sharma A et al that occurs most commonly in the lumbar spine particularly at L4-L5 region [1]. Lechowski et al presented 11 cases of intradural lumbar disc herniations from 2030 (<0.05%) patients treated surgically for intervertebral disc prolaps while Schisano G et al reported nine cases of intradural herniations (1.51%) in 593 cases of ruptured lumbar disc that underwent surgery from 1980 to 1992 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lechowski et al presented 11 cases of intradural lumbar disc herniations from 2030 (<0.05%) patients treated surgically for intervertebral disc prolaps while Schisano G et al reported nine cases of intradural herniations (1.51%) in 593 cases of ruptured lumbar disc that underwent surgery from 1980 to 1992 [6]. All authors concluded that the frequency of intradural disc rupture is very low [1,6,7].…”
Section: Introductionmentioning
confidence: 99%